Control of Shape Memory Alloy Actuator via Electrostatic Capacitive Sensor for Meso-scale Mirror Tilting System - Kim, Baekgyeom; Lee, Doohoe; Kim, Dongjin; Han, Seungyong; Kang, Daeshik; Kim, Uikyum; Kohl, Je Sung (Proceedings - IEEE International Conference on Robotics and Automation, 2023)
Shape memory alloy (SMA) has superior actuation capability over the limit of the scale. However, inherently low controllability is a primary issue that hinders practical usage. To address this challenge, this paper presents an SMA-based artificial muscle actuator capable of the displacement sensing through the capacitive sensor. To realize sensing capability, the theoretical model-based design and fabrication process are proposed. Here, we show that the actuator can be controlled at intervals of 100 μm as well as maintaining sensing capability while lifting 90 times heavier than its weight. To exhibit the usefulness of the actuator to an optical device, we integrate the actuator into the mirror tilting device, which has 20 degrees tilting angle. We expect that the proposed actuator can overcome the scale limit of meso-scale devices, which require payload capacity and controllability, simultaneously.
Keywords: Actuation capability; Artificial muscle actuator; Control of shape; Design-process; Displacement sensing; Fabrication process; Meso scale; Model-based design; Shape memory alloy actuators; Theoretical modeling